Low-loss beam synthesizing network based on Epsilon-near-zero (ENZ) medium for on-chip antenna array - Hao Li; Ziheng Zhou; Yongzhi Zhao; Yue Li (Chip, 2023)
ABSTRACT: Beam synthesizing antenna arrays are essentially demanded for on-chip millimeter wave and terahertz systems. In order to achieve a particular radiation beam, specific amplitude and phase distributions are required for all the array elements, which is conventionally realized through a properly designed feeding network. In the current work, a low-loss feeding network design approach based on epsilon-near-zero (ENZ) medium was proposed for large-scale antenna arrays with different beam requirements. Due to the infinite wavelength within the ENZ medium, a newly-discovered stair-like resonant mode was adopted for assigning a uniform phase distribution to each element, while the amplitudes and positions of these elements were optimized for generating particular beams. To implement the design philosophy in a low-loss manner, a hollow air-filled waveguide near cutoff frequency was employed to emulate the ENZ medium, and the bulk silicon microelectromechanical systems (MEMS) micromachining technology was utilized for chip-scale integration. As a specific example, a low-sidelobe antenna array at 60.0 GHz was designed, which realized an impedance bandwidth of 2.57%, a gain of 13.6 dBi and a sidelobe level as low as -20.0 dB within the size of 0.5 × 3.4λ02. This method is also compatible with a variety of applications, such as the high-directivity antenna array, non-diffractive Bessel beam antenna array, and so on. Based on this innovative concept of applying ENZ medium to the on-chip antenna array, it shows the advantages of simple structure and low loss for on-chip beam synthesis without complex lossy feeding networks.